A case report of hydronephrosis caused by imperforate hymen in an infant. Issue 45 (6th November 2020) - Zhang, Meixiang; Luo, Yingchun; Wang, Sheng; Wang, Siyao; Kuang, Haiyan
Abstract: Rationale: Hydronephrosis, mostly caused by ureteropelvic junction obstruction, rarely occurs in infants. However, imperforate hymen atresia in female infants may cause hydronephrosis, even though it is rare. Patient concerns: A 3-month-old female infant was admitted to our hospital for frequent crying. There was no significant past medical history. Diagnoses: Following ultrasound imaging, the patient was diagnosed with hydronephrosis possibly caused by imperforate hymen. Interventions: The infant underwent hymenotomy with a cruciate incision to prevent future complications such as acute renal injury. Outcomes: Hydronephrosis resolved after the operation. The outcome was very good, with no complications in the postoperative period. Conclusions: Early ultrasound diagnosis plays a significant role in the management and treatment of infant patients. Ultrasound is the mandatory imaging technology for determining the cause of hydronephrosis.